THE EFFECT OF DYNAMIC GEOMETRY SOFTWARE ON SEVENTH GRADE STUDENTS' UNDERSTANDING OF QUADRILATERALS - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2010)
The aim of this study was to investigate the effects of dynamic geometry activities on 7th grade students' understanding of quadrilaterals that include the properties of quadrilaterals and the relationship between quadrilaterals. The study was carried out at two elementary school sites in Turkey at the second term of the 2008-09 academic year, for six weeks. There were 44 7th grade students in the experimental study. A geometry achievement test prepared by the researcher was given to each group as the pre and post tests. The quadrilaterals activities were done with Geometer's Sketchpad software in the experimental group. On the other hand, the paper and pencil activities that include the same topics were used with the control group by the same teacher. After a six week implementation of the activities, a post test was given to both groups of students. The data from geometry achievement test, activities, classroom observations and interviews were analyzed. According to the post test results, a significant difference was found between experimental group and control group [t((42))=2.028, p<.05]. During the activities the students were asked to define a quadrilateral however their definitions seemed to be as descriptions rather than as definitions. Consequently, the lessons throughout the dynamic geometry software are found to be more effective in the teaching of quadrilateral subject. Although not intended, the students' Van Hiele geometrical thinking level also improved.
Keywords: Dynamic geometry; quadrilaterals; hierarchical classification